ERA FINTECH: PELUANG DAN TANTANGAN BAGI EKONOMI SYARIAH - Rokhmat Subagiyo (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
Changes in digital technology occur very quickly because of the industrial revolution 4.0. Human behavior has changed in accessing financial services or FinTech. Modern online businesses replace traditional businesses. Indonesia as one of the prima donna to develop FinTech. The Islamic financial industry is more stable and stronger to survive than the conventional financial industry. FinTech sharia opportunities are still wide open because it provides solutions for needs that cannot be served by conventional financial services. The results of the study include: (1) FinTech Sharia is able to realize the transparency of financial activities; (2) creating opportunities for customers both households and businesses to access sharia financial services; (3) providing sharia investment opportunities; (4) fintech has the potential to pose risks to consumers. Recommendation given: Islamic economics is important to answer the challenges of FinTech by issuing products or policies that are in accordance with the development of FinTech and Islamic principles.